1994
DOI: 10.1093/glycob/4.6.797
|View full text |Cite
|
Sign up to set email alerts
|

Human serum contains a chitinase: identification of an enzyme, formerly described as 4-methylumbelliferyl-tetra-N-acetylchitotetraoside hydrolase (MU-TACT hydrolase)

Abstract: Since 1988 an endoglucosaminidase, provisionally named MU-TACT hydrolase, has been known that hydrolyses the artificial substrate 4-methylumbelliferyl-tetra-N-acetyl-chitotetraoside (MU-[GlcNAc]4, where GlcNAc is N-acetylglucosamine). The biological function of the enzyme was unknown. In this paper evidence is presented showing that this endoglucosaminidase from human serum is in fact a chitinase that is different from lysozyme. The facts sustaining this finding are: (i) the identification of the products form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…There are some reports showing the existence of chitinase activities in the sera of the goat, guinea pig, and human [10,[12][13][14]. By use of the present immunoblotting, we also tested the possibility that the antibody against bovine gut chitinase could detect protein bands in the plasma of other animal species (Fig.…”
mentioning
confidence: 94%
“…There are some reports showing the existence of chitinase activities in the sera of the goat, guinea pig, and human [10,[12][13][14]. By use of the present immunoblotting, we also tested the possibility that the antibody against bovine gut chitinase could detect protein bands in the plasma of other animal species (Fig.…”
mentioning
confidence: 94%
“…The same effect of free GalNAc was observed for the Jack bean enzyme, although the degree of inhibition was higher (24%). It is improbable that step 1 of the above reaction pathway (removal of the outer G1cNAc) is catalyzed by the exo-enzyme a-N-acetylhexosaminidase, since in earlier work we already demonstrated that under the conditions employed here, /3-N-acetylhexosaminidase from Jack bean was virtually inactive towards this substrate (17). The above results suggested that the outer G1cNAc residue of MU-[G1cNAc]2 was removed by a chitobiase-like $-N-acetylglucosaminidase.…”
Section: Enzyme Activity Levels In C Albicans During Various Stages mentioning
confidence: 87%
“…The mixtures were kept on ice for 15 min and were then centrifuged for 10 min at 12,000 X g. The supernatant (1,000,u1) was neutralized with 60,u1 of 2.0 M NaOH and desalted on small columns of Bio-Rad AG 50W-X8 (H+ form; bed-volume 500,u1), followed by Bio-Rad AG 1-X8 (acetate form; bed-volume 500,u1). The resulting preparations were analyzed by high-pressure liquid chromatography (HPLC) on a CarboPac PA-100 column (HPAEC-PAD), as we described before (17).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chitinase was found in vertebrates, in human, and in guinea pig serum (Overdijk & Van Steijn 1994, Overdijk et al 1996. Chitin is a component in the sheat of Brugia malayi (Fuhrman & Piessens 1985), Onchocerca volvu- …”
Section: Discussionmentioning
confidence: 99%